Cadaveric Study for Safe Elevation of a Profunda Artery Perforator Flap: Anatomy of the Perforators and Obturator Nerves - Nam, Yong-Seok; Kim, Hyung Bae; Kim, Sang Hyun; Eom, Jin Sup; Han, Hyun Ho (Journal of Reconstructive Microsurgery, 2023)
Background This cadaveric study aimed to describe the anatomy of the profunda artery perforators (PAPs).Methods In total, nine free cadavers with 18 upper thighs were dissected, 12 of which were from female cadavers, and 6 were from male cadavers. The average age of the cadavers was 84.7 ± 4.2 years. Dissection was performed to evaluate the anatomic position and characteristics of the femoral PAPs. The perforator distance from the gluteal sulcus, number of perforators, perforating muscles, diameter of the perforators, origin of the perforators, and number of nerves passing above and below the perforators were determined.Results The average number of perforators that penetrate the adductor magnus muscle was 2.5. The average distance from the origin of the perforators to the gluteal sulcus was 71.72 ± 28.23 mm. The average numbers of the obturator nerves passing above and below the perforator in the adductor magnus muscle were 1.3 (range, 0–4) and 0.7 (range, 0–2), respectively.Conclusion The results provide a detailed anatomic basis for the PAP flap. The perforators of a PAP flap may be included in a flap with a transverse design. Sacrificing the small obturator nerves during dissection may not lead to significant donor site morbidity.
Keywords: profunda artery perforator; cadaver; autologous breast reconstruction; flap